2014
DOI: 10.1007/s12031-014-0332-5
|View full text |Cite
|
Sign up to set email alerts
|

The Expression Changes of Myelin and Lymphocyte Protein (MAL) Following Optic Nerve Crush in Adult Rats Retinal Ganglion Cells

Abstract: Myelin and lymphocyte protein (MAL), a component of compact myelin, is highly expressed in oligodendrocytes and Schwann cells. It has been reported that MAL may play a vital role in the process of neuronal apoptosis following acute spinal cord injury. However, acquaintance regarding its distribution and possible function in the retina is limited. Therefore, in a rodent model of optic nerve crush (ONC), the dynamic changes of MAL in retina was detected. The expression of MAL was mainly located in the retinal ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Thus, the activation of caspase-3 is involved in both the extrinsic and the intrinsic apoptotic pathway [30]. A growing body of evidence demonstrates that caspase-3 activation in RGCs is up-regulated after ON injury [39-41], and inhibition of caspase-3 activation increase the survival of RGCs [28, 37]. In our present study, the increased expression of cleaved-caspase-3 in NeuN-positive RGCs suggested a possible activation of caspase-3-dependent pathway after ONC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the activation of caspase-3 is involved in both the extrinsic and the intrinsic apoptotic pathway [30]. A growing body of evidence demonstrates that caspase-3 activation in RGCs is up-regulated after ON injury [39-41], and inhibition of caspase-3 activation increase the survival of RGCs [28, 37]. In our present study, the increased expression of cleaved-caspase-3 in NeuN-positive RGCs suggested a possible activation of caspase-3-dependent pathway after ONC.…”
Section: Discussionmentioning
confidence: 99%
“…Only left optic nerve of the rats was crushed as described in previous studies [39, 49] with slight modification. Briefly, after general anesthesia induced by 10 % chloral hydrate, the ON was exposed and isolated after the gently rotated downward in the orbit.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They are found throughout the brain and spinal cord of the CNS and are one of the few mobile cell types in the CNS, which can proliferate readily at the sign of injury (Ransohoff and Brown, 2012). Oligodendrocytes are responsible for myelination of axons facilitating rapid conduction of the action potential from one node of Ranvier to the next (Huang et al, 2014). …”
Section: Use Of Cells In the In Vitro Modeling Of The Cnsmentioning
confidence: 99%